Histopathological Finding of Microdamage Accumulation in Atypical Subtrochanteric Femoral Fracture. (22nd March 2021) - Watanabe, Yo; Kondo, Naoki; Fukuhara, Tomomi; Imai, Norio; Yamada, Masahiko; Endo, Naoto
Abstract : Atypical femoral fracture is a low-energy stress fracture in the subtrochanteric region or the femoral shaft and is a complication of the long-term use of bisphosphonates. Histopathological findings of atypical femoral fractures have not been clarified. Herein, we report the case of a 61-year-old woman who fell while walking, which prompted her to visit our facility. She had a 7-year history of alendronate use to treat osteoporosis. A radiograph showed an atypical subtrochanteric femoral fracture, following which she underwent a primary surgery, where an intramedullary femoral nail was used. Implant breakage was discovered 8 weeks after the primary surgery. The patient underwent a revision surgery in which the entry point for the revised intramedullary hole was created to prevent varus position. The lag screw was successfully inserted into the center of the femoral head. Cancellous bone, isolated from the right ilium, was autogenously implanted into the fracture site. Fracture healing was promoted using low-intensity pulse ultrasonography. Callus formation was detected on a radiograph, and full weight-bearing was advised 12 weeks after the revision surgery. The fracture had healed completely at 13 months after the revision surgery. The patient was able to walk without support and could independently perform activities of daily life. Laboratory findings suggested that the concentrations of her bone formation markers were normal, while those of bone resorption markers were elevated. Iliac bone histomorphometry did not reveal severely suppressed bone turnover. In the cortex of fracture site, the lacunar density was markedly lower than the osteocyte density, and microcracks were detected, suggesting impaired osteocyte function and a low potential for fracture healing. This case is notable because it helps to clarify the histopathological findings of atypical femoral fractures.